ABSOLUTIVE VERBS AS A SUBSTRATE OF FORMAL-GRAMMATICAL AND SEMANTIC SYNTACTICAL STRUCTURES OF UNEXTENDED SENTENCES - Liudmyla V. Suprun; Volodymуr M. Suprun (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The main thesis of the article is that the semantics of a sentence is determined by the lexical content of its structure. The main goal of the study is to analyze the predicative center of unextended verb sentences without obligatory predicate components, which is modeled by verbs of absolute semantics. We will try to solve the following problems: 1) to find out the role of absolute verbs in the mechanisms of formation and implementation of unextended verb sentences; 2) to identify the main parameters of the formal-grammatical structure of unextended constructions; 3) to analyze the features of semanticsyntactic organization of unextended sentences. In research we use the methods of linguistic analysis, they are descriptive (in considering the phenomena of one level), comparative (analyzing the components of different levels to identify interlevel relationships), statistical calculations and quantitative characteristics, interpretive analysis (interpretation of semantics of certain syntactic units), transformation (transformation of a certain syntactic structure in order to characterize it). It was found that the main criteria for distinguishing absolute verbs from others are: semantic (denotative), grammatical (syntactic connections) and the nature of connections with dependent words or components in the sentence structure. The basis for the formation of formal-grammatical and semantic-syntactic structure of unextended sentences are absolute verbs, which by their internal potential do not predict, do not open the obligatory right-hand positions to fill them with words with objective or circumstantial meaning. The correlation of absolute verbs with the realities of extralinguistic reality provides their own phonemic composition because such verbs have a sufficient semantic content. If necessary, absolute verbs can be extended by dependent words, but this is not necessary, because the verb feature conveyed by the absolute token is semantically complete. It is observed that the subject of an unextended two-member sentence verb is not explained by secondary members, is not complicated and is expressed by the words with absolute meaning, with complete semantics, which are the names of persons, beings, objects, phenomena, abstract concepts. The predicate of an unextended two-member sentence is represented by words that do not allow communicative development of the statement, are characterized by complete semantics and mean the state of the person; procedural state of the subject; transition from one state to another; specific action of a person as his permanent occupation, specialty. It is stated that the main member of an unextended one-member verb sentence coincides in form with the predicate of a two-member sentence but combines the meaning of a logical subject and a predicate and is expressed by word forms that are able to reflect the corresponding fragment of reality. Analysis of unextended verb sentences without the obligatory predicate components showed that their semantics is a complex of semantic components of different nature. In the semantic-syntactic aspect, the considered units have certain differential features, which are caused primarily by the peculiarities of absolute predicate verbs, which are characterized by self-sufficient semantic content. The results of our scientific research are designed to help solve certain issues of syntax of modern Ukrainian literary language. Research materials can be used in teaching university courses “Modern Ukrainian literary language”, “Stylistics of the Ukrainian language”, “History of Ukrainian literary language”, “History of Ukrainian literature of the 20th century”, as well as in the process of creating works on the life and works of Oles Honchar.